Teodemokrasi dalam Konsepsi Negara Islam: (Studi Komparasi Pemikiran Abu al-A’la Maududi dan Ayatullah Khomeini) - Wafa Ilmi, Vika; Imam Ghazali Said; Zainal Fanani (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2025)
This research examines the thoughts of Abu al-A'la al-Maududi and Ayatollah Khomeini on theodemocracy in the Islamic state through a comparative study. Using a qualitative approach and literature research method, this study analyzes their primary works, particularly al-Hukumah al-Islamiyah, along with relevant secondary sources. The findings show that despite coming from different madhhab backgrounds - Sunni and Shia - both figures share fundamental views on the unity of Islam and state, as well as criticism of the secular Western democratic system. However, significant differences exist in their interpretation of theodemocracy, especially regarding state leadership. Maududi developed al-Hakimiyah al-Ilahiyah emphasizing collective sovereignty of the ummah, while Khomeini's Wilayah al-Faqih places ulama as the highest authority. These differences reflect in their proposed state structures: Maududi advocated classical trias politica, while Khomeini developed a system with Faqih as supreme supervisor. This research reveals that successful implementation of Islamic state concepts depends not only on ideological strength but also on compatibility with local socio-cultural and political contexts, as evidenced in Pakistan and Iran's experiences.